Soluble intercellular adhesion molecule (ICAM)-1 detects invasive fungal infections in patients following liver transplantation. (2nd October 2020) - Decker, Sebastian O.; Incamps, Anne; Wilk, Henryk; Uhle, Florian; Bruckner, Thomas; Heininger, Alexandra; Zimmermann, Stefan; Mehrabi, Arianeb; Mieth, Markus; Weiss, Karl Heinz; Weigand, Markus A.; Brenner, Thorsten
Abstract: Purpose: Despite antifungal prophylaxis, liver transplanted patients are endangered by invasive fungal infections (IFI). Routinely used microbiological procedures are hallmarked by significant weaknesses, which may lead to a delay in antifungal treatment. Methods: Culture-based fungal findings, routinely used biomarkers of infection/inflammation (e.g., procalcitonin or C-reactive protein), as well as corresponding plasma concentrations of soluble Intercellular Adhesion Molecule (ICAM)-1 were analysed in 93 patients during a period of 28 days following liver transplantation (LTX). Results: Plasmatic sICAM-1 was significantly elevated in patients affected by an IFI within the first 28 days in comparison to fungally colonised or unobtrusive LTX patients. sICAM-1 might therefore be helpful for the identification of IFI patients after LTX (e.g., Receiver Operating Characteristic (ROC)-Area Under the Curve (AUC): 0.714 at 14d after LTX). The diagnostic performance of sICAM-1 was further improved by its combined use with different other IFI biomarkers (e.g., midregional proadrenomedullin). Conclusion: The diagnostic deficiencies of routinely used microbiological procedures for IFI detection in patients after LTX may be reduced by plasmatic sICAM-1 measurements. Clinical Trial Notation . German Clinical Trials Register: DRKS00005480